MODELS OF THE 5 PORTERS COMPETITIVE FORCES METHODOLOGY CHANGES IN COMPANIES STRATEGY DEVELOPMENT ON COMPETITIVE MARKET - Sergey I Zubin; Timur A. Tultaev (Статистика и экономика, 2016)
There are some different types of approaches to 5 Porters Forces model development in thisarticle. Authors take up the negative attitude researcher reasons to this instrument and inputsuch changes in it, which can help to ﬁ nd the best way to companies growing up on competitive market.